The impact of oral anticoagulation on time to surgery in patients hospitalized with hip fracture. Issue 5 (November 2015) - Tran, Thomas; Delluc, Aurélien; de Wit, Carine; Petrcich, William; Le Gal, Grégoire; Carrier, Marc
Abstract: Introduction: Current clinical guidelines recommend expedited repair of hip fracture to reduce morbidity and mortality. A significant number of hip fracture patients have concomitant cardiovascular disease requiring anticoagulation. Vitamin K antagonists (VKAs), which have been traditionally used, might be associated with an increased time to surgery (TTS) and it remains unknown what effect direct oral anticoagulants (DOACs) have on this metric. Our objective is to determine how anticoagulation with a VKA or DOAC affects TTS. Materials and methods: This is a case control study comparing TTS in consecutively admitted hip fracture patients receiving either a DOAC or VKA with age- and gender-matched controls between January 1, 2010 and March 24, 2014. The primary end point is TTS, which is defined as the time elapsed from admission to surgery. Secondary end points include the rate of stroke, death, bleeding and VTE during admission. Results: Of 2258 patients, 233 were on a VKA while 27 were on a DOAC. Median TTS seems to be longer in patients receiving a DOAC or a VKA when compared to controls. (40 h vs. 26.2 h). The DOAC group tended to have longer median TTS when compared to the VKA groups (66.9 h vs. 39.4 h) There was no difference in the rate of stroke, death, bleeding and VTE during admission. Conclusions: Patients on anticoagulation prior to admission for hip fracture experienced longer delays in surgery when compared to patients not receiving anticoagulation. Patients on a DOAC experienced the longest surgical delay. Highlights: We compare hip fracture repair time in patients on no anticoagulation, VKA and DOACs. DOAC patients waited longer than guideline recommendation for hip repair. Patients on any oral anticoagulation waited longer for surgery. There is no difference in stroke, death, VTE or bleeding between groups.